Cost distance models to predict contact between bighorn sheep and domestic sheep. (22nd July 2022) - Anderson, Kathleen; Cahn, Maya L.; Stephenson, Thomas R.; Few, Alexandra P.; Hatfield, Brian E.; German, David W.; Weissman, Jonathon M.; Croft, Brian
Abstract: Infectious disease transmission from domestic sheep threatens the persistence of bighorn sheep ( Ovis canadensis) populations throughout western North America. Quantifying spatial separation between the 2 species is an essential component in assessing the risk of disease transmission. We present a spatial analysis to evaluate infectious disease risks for endangered Sierra Nevada bighorn sheep ( O. c. sierrae ; hereafter Sierra bighorn sheep). Our approach accounted for spatial separation between the species as well as the configuration of resources that influences Sierra bighorn sheep movement. We assessed the potential for contact by predicting where Sierra bighorn sheep were likely to be located and travel. We combined a resource selection probability function with a cost distance analysis to quantify the risk of grazing domestic sheep in proximity to Sierra bighorn sheep core home range from a habitat perspective. We compared our approach to a standard buffer approach and determined that our cost distance model better quantified how risk varied among grazing parcels. Sierra bighorn sheep selected and traveled within habitat that included escape terrain. Our model, which included a log normal transformation, characterized the high relative cost (i.e., reduced likelihood) to traveling beyond selected habitat and predicted that such movement is less likely. As a result, our habitat‐based risk threshold was 48% smaller in area than the standard buffer area that included landscape that bighorn did not use. Our method establishes a risk threshold that can be used by land managers to optimize public and private grazing regimes and minimize the risk of disease transmission. Abstract : Risk of disease transmission between domestic sheep and bighorn sheep is the most serious threat to bighorn conservation throughout the western United States and Canada. Managing this risk is a major challenge for land managers. We developed a spatially explicit model to quantify the potential for contact between bighorn and domestic sheep.